Can follow-up examination of tuberculosis patients be simplified? A study in Chhattisgarh, India. - Debashish Kundu (Public Library of Science (PLoS), 2012)
Background Each follow-up during the course of tuberculosis treatment currently requires two sputum examinations. However, the incremental yield of the second sputum sample during follow-up of different types of tuberculosis patients has never been determined precisely. Objectives To assess the incremental yield of the second sputum sample in the follow-up of tuberculosis patients under the Revised National Tuberculosis Control Programme (RNTCP) in Chhattisgarh, India. Methodology A record review of tuberculosis (TB) patients registered in 2009 using a structured proforma from two sources, Tuberculosis and Laboratory Register, was undertaken in the six districts of Chhattisgarh, India. Results In smear positive cases, of 10,048 follow-up examinations, 45 (0.5%) were found to be smear positive only on the second sputum when the result of the first sample was negative. In smear negative pulmonary and extra pulmonary TB patients, of 6,206 follow-up smear examinations, 11(0.2%) were found to be smear positive. Conclusions The incremental yield of a second smear examination was very low, indicating that examination of one sputum sample is enough during follow-up among TB patients. There is insufficient yield to support sputum smear microscopy for monitoring smear negative pulmonary TB and extra pulmonary TB patients. These results indicate that the follow-up smear microscopy can be substantially simplified with favourable resource implications.